The tourism function of the castles of the Knights of the Teutonic Order in Poland - Musiaka, Łukasz (Turyzm/Tourism, 2013)
The author’s main objective is to define the level of development of the tourism function of the Teutonic Order castles found in the area of contemporary Poland. The author has taken into account both well-preserved and renovated castles, as well as those in a state of ruin. In order to achieve his goal, he analysed forms of castle development and numbers of tourists, which is the main measure of the tourism function. The final stage of the research was to define the tourism rank of the castles studied.